Analisis Faktor-Faktor Yang Mempengaruhi Semangat Kerja Karyawan Generasi Milenial Pada Perusahaan Ekspedisi - Yuyu Ruhayu (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine and analyze factors that can influence the work spirit of millennial generation employees at expedition companies. The research method used is analysis in the form of mix methods which can be carried out through gradual quantitative-qualitative analysis, namely quantitative data analysis followed by collecting qualitative data analysis. The results of this research show that the most dominant factors influencing the work spirit of millennial generation employees are work environment factors 92%, organization 88%, compensation and benefits 85%, and leadership style 83%. Keywords: Human Resources, Employee Morale, and Millennial Generation